Impact of type and severity of postoperative complications on long‐term outcomes after colorectal liver metastases resection. Issue 2 (26th April 2020) - Fernández‐Moreno, María‐Carmen; Dorcaratto, Dimitri; Garcés‐Albir, Marina; Muñoz, Elena; Arvizu, Ricardo; Ortega, Joaquín; Sabater, Luis
Abstract: Background and Objectives: Postoperative complications (POCs) after hepatic resection for colorectal liver metastases (CRLM) adversely affect long‐term survival. The aim of this study was to analyze the effect of POC etiology and severity on overall survival (OS) and disease‐free survival (DFS). Methods: A retrospective study of 254 consecutive hepatectomies for CRLM was performed. Univariate and multivariate analyses were performed to determine the effects of demographic, tumor‐related and perioperative variables on OS and DFS. A 1:1 propensity score matching (PSM) was then used to compare patients with different POC etiology: infective (Inf‐POC), noninfective (Non‐inf POC), and no‐complications (No‐POC). Results: Inf‐POC, Non‐inf POC, and No‐POC patients represented 18.8%, 19.2%, and 62% of the sample, respectively. In univariate and multivariate analyses infectious POC were independent risk factors for decreased OS and DFS. After PSM, Inf‐POC group presented decreased OS and DFS when compared with Non‐inf POC (5‐year OS 31.8% vs 51.6%; P = .05 and 5‐year DFS 13.6% vs 31.9%; P = .04) and with No‐POC (5‐year OS 29.4% vs 58.7%; P = .03 and 5‐year DFS 11.8% vs 39.7%; P = .03). There were no differences between Non‐inf POC and No‐POC patients. POC severity calculated using the Comprehensive Complications Index did not influence OS and DFS before and after PSM. Conclusion: The negative oncological impact of POCs after CRLM resection is determined by infective etiology not by severity.